2016
DOI: 10.1080/09593330.2016.1164249
|View full text |Cite
|
Sign up to set email alerts
|

A toxicity assessment of 30 pharmaceuticals using Aliivibrio fischeri: a comparison of the acute effects of different formulations

Abstract: Considerable quantities of different classes of drugs are consumed annually worldwide. These drugs, once disposed, often remain stable, even after conventional or advanced treatments. Although there have been a number of studies on the potential harm caused by drugs when released into the environment, few studies have investigated the toxicity of pharmaceutical excipients. In the present study, the acute toxicity of 30 drugs was tested to Aliivibrio fischeri. Ten different active ingredients were investigated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…Recently, metformin was found to alter the distribution of microbiota and regulate the host glucose metabolism process by regulating the microbiota in gut ecology [20]. Metformin can alter the morphology, growth, locomotor activity, and reproduction of bacteria in aquatic environments [35]. In the present study, we demonstrated that metformin inhibited the growth of E. coli , which has also been reported for Helicobacter pylori [36].…”
Section: Discussionsupporting
confidence: 85%
“…Recently, metformin was found to alter the distribution of microbiota and regulate the host glucose metabolism process by regulating the microbiota in gut ecology [20]. Metformin can alter the morphology, growth, locomotor activity, and reproduction of bacteria in aquatic environments [35]. In the present study, we demonstrated that metformin inhibited the growth of E. coli , which has also been reported for Helicobacter pylori [36].…”
Section: Discussionsupporting
confidence: 85%
“…The maximum concentration in plasma (Cmax) was 4.69 ng/mL and 4.92 ng/mL for dexchlorpheniramine maleate and the reference standard, respectively (Moreno et al, 2010). Jacob et al (2016) evaluated the acute toxicity of dexchlorpheniramine maleate in A. fischeri by measuring the luminescence of the bacteria after 30 minutes of contact with the drug. The authors reported that dexchlorpheniramine maleate in any formulation (generic, similar, or reference) did not exhibit toxicity in their experimental model.…”
Section: Peripheral Blood Mononuclear Cell (Pbmc) Isolationmentioning
confidence: 99%
“…Contudo, tal estudo não faz alusão aos desreguladores endócrinos ou aos antibióticos (BERGMAN et al, 2012). No Brasil, encontram-se poucos trabalhos sobre a toxicidade desses microcontaminantes; um desses foi realizado por Jacob et al (2016) Figura 1 -Fontes e destinos dos fármacos e desreguladores endócrinos nos recursos hídricos.…”
Section: De Acordo Com a Agência De Proteção Ambiental Dos Estados Ununclassified